1996
DOI: 10.1111/j.1475-4754.1996.tb00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Only Time Will Tell: A Review of the Methodology of Direct Rock Art Dating

Abstract: Epistemology has not kept pace with the progress experienced in the direct dating of rock art. This paper reviews the experimental methods that have been developed in recent years. While many do provide important information about the possible age of rock art, it is of concern that the precipitate archaeological interpretations these data are used for are often not warranted. Some are attributable to not understanding the severe qualifications that apply to most dating results, others perhaps to over‐enthusias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…Dreamtime Superhighway: an analysis of Sydney Basin rock art and prehistoric information exchange regional patterns for the Sydney region The problem of demonstrating contemporaneity between art and deposit relates primarily to the fact that parietal art, until recently, could not be directly dated. Theoretically AMS radiocarbon dating is the solution to this issue, but this technique is still in its adolescence (Keyser 2001) because of the relative newness of the techniques and the lack of theorising about applicability of these techniques to art assemblages generally (see Beck et al 1998;Bednarik 1996;Hyman and Rowe 1997;McDonald 2000c;McDonald et al 1990;Rosenfeld and Smith 1997).…”
Section: The Contemporaneity Of Art and Depositmentioning
confidence: 99%
“…Dreamtime Superhighway: an analysis of Sydney Basin rock art and prehistoric information exchange regional patterns for the Sydney region The problem of demonstrating contemporaneity between art and deposit relates primarily to the fact that parietal art, until recently, could not be directly dated. Theoretically AMS radiocarbon dating is the solution to this issue, but this technique is still in its adolescence (Keyser 2001) because of the relative newness of the techniques and the lack of theorising about applicability of these techniques to art assemblages generally (see Beck et al 1998;Bednarik 1996;Hyman and Rowe 1997;McDonald 2000c;McDonald et al 1990;Rosenfeld and Smith 1997).…”
Section: The Contemporaneity Of Art and Depositmentioning
confidence: 99%
“…For example, rock art has been dated by luminescence dating of sediments deposited over the art (and sometimes under it) by mud-daubing insects . Dating of quartz grains incorporated in or under rock art has also been considered (Bednarik, 1996).…”
Section: Suitability For Datingmentioning
confidence: 99%
“…While both calcium oxalate and mud wasp nest samples each have limitations for radiocarbon dating (cf. Aubert 2012;Bednarik 1996Bednarik , 2000Bednarik , 2002Bednarik , 2007David et al 2013;Gillespie 1997;Rosenfeld and Smith 1997), our study has found that multiple radiocarbon age determinations from these two different substances can together generate robust dates for rock art.…”
Section: Introductionmentioning
confidence: 99%